High-strength flexible thermal insulation material and preparation method thereof

By compounding oxide fiber fiber and phenol fiber and alumina nano -slices, and carbonizing in an inert atmosphere, the problem of insufficient toughness and lower pressure resistance of oxide fiber fiber insulation materials, the high -strength flexible interval The preparation of thermal materials is suitable for high temperature and high pressure environment.

CN119349976APending Publication Date: 2025-01-24AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411461161.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Due to the high brittleness of the fiber material, zirconia fiber insulation materials have insufficient toughness and low compressive strength, which makes it difficult to meet the application needs of harsh mechanical properties.

Method used

By combining zirconium oxide fiber with materials such as phenolic fiber and alumina nanosheets, and carbonizing it in an inert atmosphere, a high-strength flexible thermal insulation material is formed.

Benefits of technology

It significantly improves the flexibility and tensile strength of zirconia fiber insulation materials, enhances the overall strength and insulation performance of the material, and is suitable for high temperature and high pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091905930000131
    Figure BDA0005091905930000131
Patent Text Reader

Abstract

The invention relates to a high-strength flexible thermal insulation material and a preparation method thereof. The method comprises the following steps: carrying out first stirring dispersion on a system containing phenolic fibers, zirconium oxide fibers and water to obtain a first dispersion system; adding aluminum oxide nanosheets and a phosphate solution into the first dispersion system, carrying out second stirring dispersion to obtain a second dispersion system, and then carrying out papermaking on the second dispersion system to obtain a papermaking material; and placing the papermaking material in a shaping mold for shaping and drying, and carbonizing in an inert atmosphere to prepare the high-strength flexible thermal insulation material. According to the invention, the flexibility and tensile strength of the zirconium oxide fiber thermal insulation material are effectively improved, and a solid material foundation is laid for application of zirconium oxide fibers in an environment with harsh mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zirconium oxide fiber thermal insulation materials, and in particular relates to a high-strength flexible thermal insulation material and a preparation method thereof. Background Art

[0002] Zirconia fiber thermal insulation materials have the characteristics of ultra-high temperature resistance and low thermal conductivity, and are widely used in thermal protection fields in extreme environments such as aerospace. However, due to the high brittleness of the fiber material itself, zirconia fiber thermal insulation materials have the problems of insufficient material toughness and low compressive strength.

[0003] In order to improve the problem of insufficient mechanical properties of zirconia fiber insulation materials, researchers have combined zirconia fibers with carbon fibers to improve the flexibility of the material. However, since this process only improves the flexibility of the material by physically overlapping fibers of different sizes, there is no chemical cross-linking between the fibers, which limits the improvement in the flexibility of the composite material. In addition, researchers have added high-temperature glue to improve the strength of the material. The material strength has increased, but the material has become more brittle and the flexibility has decreased, and the improvement in the overall performance of the material has been limited. Therefore, it is urgent to find new methods to improve the flexibility and strength of zirconia fiber insulation materials.

[0004] In summary, it is very necessary to provide a high-strength flexible thermal insulation material and a preparation method thereof. Summary of the invention

[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a high-strength flexible thermal insulation material and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing a high-strength flexible thermal insulation material, the method comprising the following steps:

[0007] (1) subjecting a system comprising phenolic fiber, zirconium oxide fiber and water to a first stirring dispersion to obtain a first dispersed system;

[0008] (2) adding alumina nanosheets and phosphate solution to the first dispersed system and performing a second stirring dispersion to obtain a second dispersed system, and then papermaking the second dispersed system to obtain a papermaking material;

[0009] (3) The papermaking material is placed in a shaping mold for shaping and drying, and then carbonized under an inert atmosphere to obtain a high-strength flexible thermal insulation material.

[0010] Preferably, in step (1): the mass ratio of the zirconium oxide fiber to the phenolic fiber is (4-19):1.

[0011] Preferably, in step (1): the diameter of the zirconium oxide fiber is 1 to 10 μm; and / or the diameter of the phenolic fiber is 200 to 1000 nm.

[0012] Preferably, in step (1), the rotation speed of the first stirring and dispersing is 4000-10000 r / min, and the time of the first stirring and dispersing is 2-30 min.

[0013] Preferably, in step (2): the mass ratio of the aluminum oxide nanosheets to the phosphate solution is (1-4):(1-9); and / or the phosphate solution is an aluminum dihydrogen phosphate solution, and the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 20-50%.

[0014] Preferably, in step (2), the rotation speed of the second stirring and dispersing is 4000-10000 r / min, and the time of the second stirring and dispersing is 1-10 min.

[0015] Preferably, in step (3): the temperature of the shaping and drying is 120-200° C.; and / or the thickness of the shaping mold is 0.5-5 mm.

[0016] Preferably, in step (3), the carbonization temperature is 500-900° C., and the carbonization time is 10-20 h.

[0017] Preferably, in step (2): potassium hexatitanate K2Ti6O is added to the first dispersed system. 13 Nanowires; preferably, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowires to the aluminum oxide nanosheets is 1:(1-2).

[0018] In a second aspect, the present invention provides a high-strength flexible thermal insulation material produced by the preparation method described in the first aspect of the present invention.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] (1) The present invention uses zirconium oxide fiber and phenolic nanofiber as the main materials, and effectively improves the fiber overlap and bonding area by introducing alumina nanosheets and phosphate (such as aluminum dihydrogen phosphate) solution adhesives, thereby improving the strength of the zirconium oxide fiber thermal insulation material; at the same time, the present invention uses phenolic nanofiber as a flexible element, and forms carbon nanofibers through carbonization. The carbonization process effectively improves the interface effect between the zirconium oxide fiber and the phenolic fiber, thereby improving the strength and flexibility of the composite material; the present invention effectively improves the flexibility (flexibility) and tensile strength of the zirconium oxide fiber thermal insulation material, and lays a solid material foundation for the application of zirconium oxide fiber in environments with demanding mechanical properties.

[0021] (2) In some preferred technical solutions of the present invention, potassium hexatitanate K2Ti6O is also introduced into the material. 13 Nanowires, the present invention found that the K2Ti6O 13 The introduction of nanowires helps to further improve the strength, flexibility and thermal insulation performance of high-strength flexible thermal insulation materials; the possible reason is that K2Ti6O 13 The fibrous structure of nanowires gives them very high tensile strength and can play a role in skeleton reinforcement in composite materials. 13 Nanowires can be evenly distributed throughout the material matrix to form a dense reinforced network structure, which can effectively block crack propagation, enhance the overall strength of the material, and fill the micropores or gaps that may exist in the material, making the material structure more compact and effectively reducing defects in the material. 13 The nanometer size and aspect ratio of the nanowires give them good flexibility, which can form a good interaction with the matrix material, thereby improving the strength and flexibility of the material. 13 The fiber structure of nanowires can prevent the rapid propagation of cracks in the material. This crack-blocking effect can also significantly improve the fracture toughness of the material. Even under external stress, the material is not prone to brittle fracture, thereby enhancing its flexibility. In addition, K2Ti6O 13 The introduction of nanowires can also improve the thermal insulation performance of high-strength flexible thermal insulation materials, K2Ti6O 13 The fibrous structure of nanowires can form a complex three-dimensional network in the material, effectively blocking the heat conduction path. This network structure limits the conduction of heat inside the material, which is beneficial to improve the thermal insulation performance of the material. 13 Nanowires have a certain blocking effect on infrared radiation, reducing infrared radiation, lowering the thermal conductivity of insulation materials, and effectively enhancing the thermal insulation properties of the materials. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In a first aspect, the present invention provides a method for preparing a high-strength flexible thermal insulation material, the method comprising the following steps:

[0024] (1) subjecting a system comprising phenolic fiber, zirconia fiber and water to a first stirring dispersion to obtain a first dispersion system; in the present invention, the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system may be, for example, 5 to 15%;

[0025] (2) adding alumina nanosheets and phosphate solution to the first dispersed system and performing a second stirring dispersion to obtain a second dispersed system, and then papermaking the second dispersed system to obtain a papermaking material; in the present invention, alumina nanosheets and phosphate solution are used as composite adhesives, that is, the composite adhesive is composed of alumina nanosheets and phosphate solution, and the alumina nanosheets can be used as a part of the adhesive; the present invention does not make any specific restrictions on the papermaking, which is a conventional technology in the field; the present invention does not make any specific restrictions on the sources of phenolic fiber, zirconium oxide fiber, alumina nanosheets, etc., and products that can be directly purchased or products prepared by existing methods can be used;

[0026] (3) Placing the papermaking material in a shaping mold (hot pressing mold) for shaping and drying, and then carbonizing it under an inert atmosphere to obtain a high-strength flexible thermal insulation material; the present invention has no special requirements for the shaping and drying pressure, and those skilled in the art can make a conventional selection, for example, it can be 1 to 2 MPa.

[0027] The present invention uses zirconium oxide fiber and phenolic nanofiber as main materials, and effectively improves the fiber overlap and bonding area by introducing aluminum oxide nanosheets and phosphate (such as aluminum dihydrogen phosphate) solution adhesives, thereby improving the strength of the zirconium oxide fiber thermal insulation material; at the same time, the present invention uses phenolic nanofiber as a flexibility unit, and forms carbon nanofibers through carbonization. The carbonization process effectively improves the interface effect between the zirconium oxide fiber and the phenolic fiber, thereby improving the strength and flexibility of the composite material; the present invention effectively improves the flexibility (flexibility) and tensile strength of the zirconium oxide fiber thermal insulation material, and lays a solid material foundation for the application of zirconium oxide fiber in environments with harsh mechanical properties.

[0028] According to some specific embodiments, the preparation of the high-strength flexible thermal insulation material comprises the following steps:

[0029] ① Weigh a certain mass of phenolic fiber and zirconia fiber, place the fibers in the integrated dispersion-molding equipment, start water supply and perform the first stirring and dispersion;

[0030] ② After stirring and dispersing for a certain period of time, add alumina nanosheets and phosphate solution (such as aluminum dihydrogen phosphate solution) as a binder to the system, perform a second stirring and dispersion, and then perform rapid papermaking to obtain a papermaking material

[0031] ③ The papermaking material is placed in a shaping mold for shaping and drying, and then placed in an inert atmosphere furnace for carbonization, and finally the high-strength flexible thermal insulation material having both flexibility and strength is obtained.

[0032] According to some preferred embodiments, in step (1): the mass ratio of the zirconium oxide fiber to the phenolic fiber is (4-19):1 (for example, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1 or 19:1).

[0033] According to some preferred embodiments, in step (1): the diameter of the zirconium oxide fiber is 1 to 10 μm; and / or the diameter of the phenolic fiber (phenolic nanofiber) is 200 to 1000 nm.

[0034] According to some preferred embodiments, in step (1): the rotation speed of the first stirring and dispersing is 4000-10000 r / min (for example, 4000, 5000, 6000, 7000, 8000, 9000 or 10000 r / min), and the time of the first stirring and dispersing is 2-30 min (for example, 2, 5, 10, 15, 20, 25 or 30 min).

[0035] According to some preferred embodiments, in step (2): the mass ratio of the aluminum oxide nanosheets and the phosphate solution is (1-4): (1-9); in the present invention, preferably, the sum of the mass amounts of the aluminum oxide nanosheets and the phosphate solution is 25-60% of the sum of the mass amounts of the phenolic fiber and the zirconium oxide fiber; and / or the phosphate solution is an aluminum dihydrogen phosphate solution, and the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution (i.e., aluminum dihydrogen phosphate aqueous solution) is 20-50%.

[0036] According to some preferred embodiments, in step (2): the rotation speed of the second stirring and dispersing is 4000-10000 r / min (for example, 4000, 5000, 6000, 7000, 8000, 9000 or 10000 r / min), and the time of the second stirring and dispersing is 1-10 min (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 min).

[0037] According to some preferred embodiments, in step (3): the temperature of the shaping and drying is 120-200°C (for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C), the time of the shaping and drying is, for example, 10-20h, preferably 12h; the thickness of the shaping mold is 0.5-5mm (for example, 0.5, 1, 2, 3, 4 or 5mm); in the present invention, the thickness of the shaping mold refers to the thickness of the internal accommodating space of the shaping mold, and the thickness of the internal accommodating space of the shaping mold corresponds to the thickness of the obtained high-strength flexible thermal insulation material.

[0038] According to some preferred embodiments, in step (3): the carbonization temperature is 500-900°C (e.g., 500°C, 600°C, 700°C, 800°C or 900°C), and the carbonization time is 10-20h (e.g., 10, 12, 15, 18 or 20h).

[0039] According to some preferred embodiments, in step (2): potassium hexatitanate K2Ti6O is also added to the first dispersed system. 13 Nanowires (i.e. K2Ti6O 13 Nanowires), that is, step (2) is: adding potassium hexatitanate K2Ti6O 13 Nanowires, aluminum oxide nanosheets and phosphate are then stirred and dispersed for a second time to obtain a second dispersed system, and then the second dispersed system is paper-made to obtain a paper-made material; the present invention is to K2Ti6O 13 The source and size of the nanowires are not specifically limited, and can be directly purchased products or products synthesized by existing methods; in the present invention, the potassium hexatitanate K2Ti6O 13 The diameter of the nanowire is, for example, 80 to 120 nm, and the length is, for example, 40 to 50 μm.

[0040] The present invention preferably introduces potassium hexatitanate K2Ti6O into the material. 13 Nanowires, the present invention found that the K2Ti6O 13 The introduction of nanowires helps to further improve the strength, flexibility and thermal insulation performance of high-strength flexible thermal insulation materials; the possible reason is that K2Ti6O 13 The fibrous structure of nanowires gives them very high tensile strength and can play a role in skeleton reinforcement in composite materials. 13Nanowires can be evenly distributed throughout the material matrix to form a dense reinforced network structure, which can effectively block crack propagation, enhance the overall strength of the material, and fill the micropores or gaps that may exist in the material, making the material structure more compact and effectively reducing defects in the material. 13 The nanometer size and aspect ratio of the nanowires give them good flexibility, which can form a good interaction with the matrix material, thereby improving the strength and flexibility of the material. 13 The fiber structure of nanowires can prevent the rapid propagation of cracks in the material. This crack-blocking effect can also significantly improve the fracture toughness of the material. Even under external stress, the material is not prone to brittle fracture, thereby enhancing its flexibility. In addition, K2Ti6O 13 The introduction of nanowires can also improve the thermal insulation performance of high-strength flexible thermal insulation materials, K2Ti6O 13 The fibrous structure of nanowires can form a complex three-dimensional network in the material, effectively blocking the heat conduction path. This network structure limits the conduction of heat inside the material, which is beneficial to improve the thermal insulation performance of the material. 13 Nanowires have a certain blocking effect on infrared radiation, reducing infrared radiation, lowering the thermal conductivity of insulation materials, and effectively enhancing the thermal insulation properties of the materials.

[0041] According to some preferred embodiments, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowires to the alumina nanosheets is 1:(1-2) (e.g., 1:1, 1:1.5 or 1:2); in the present invention, preferably, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowire to the alumina nanosheet is 1:(1-2). The present invention finds that potassium hexatitanate K2Ti6O 13 Nanowires have a large surface area and a reinforcing effect in the material. The amount of nanowires added needs to be controlled within a reasonable range to avoid K2Ti6O 13 The agglomeration of nanowires affects the uniform dispersion and overall performance of the material. 13 If the amount of nanowires is too small, the reinforcement effect may not be obvious, and the strength, flexibility and thermal insulation performance of the material cannot be effectively improved. 13 Excessive use of nanowires may lead to 13 The dispersion of nanowires is difficult, which affects the uniformity of the material. It will also increase the difficulty of processing and affect the overall performance of the material.

[0042] In a second aspect, the present invention provides a high-strength flexible thermal insulation material produced by the preparation method described in the first aspect of the present invention.

[0043] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments, and those skilled in the art may make various corresponding changes and deformations according to the present invention without departing from the spirit and essence of the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention.

[0044] Example 1

[0045] ① Weigh 1 part of phenolic fiber (diameter 200-500nm) and 19 parts of zirconia fiber (1-3μm), then add water and perform a first stirring and dispersion. The rotation speed of the first stirring and dispersion is 10000r / min, and the time of the first stirring and dispersion is 2min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system is 10%.

[0046] ② Add 1 part of aluminum oxide nanosheets and 9 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 10000r / min, the time of the second stirring dispersion is 1min, and a second dispersed system is obtained; then the second dispersed system is paper-made to obtain a paper-made material.

[0047] ③ The papermaking material obtained in step ② is placed in a shaping mold (thickness 0.5 mm) and shaped and dried at 120°C for 12 hours, and then placed in an inert atmosphere furnace and carbonized at 500°C for 20 hours under an inert atmosphere (argon) to obtain a high-strength flexible thermal insulation material.

[0048] Example 2

[0049] ① Weigh 3 parts of phenolic fiber (diameter 500-1000nm) and 17 parts of zirconia fiber (3-8μm), then add water and perform a first stirring and dispersion. The rotation speed of the first stirring and dispersion is 4000r / min, and the time of the first stirring and dispersion is 30min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system is 10%.

[0050] ② Add 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0051] ③ The papermaking material obtained in step ② is placed in a shaping mold (thickness 1 mm) and shaped and dried at 200°C for 12 hours, and then placed in an inert atmosphere furnace and carbonized at 700°C for 15 hours under an inert atmosphere (argon) to obtain a high-strength flexible thermal insulation material.

[0052] Example 3

[0053] ① Weigh 4 parts of phenolic fiber (diameter 500-1000nm) and 16 parts of zirconia fiber (5-10μm), then add water and perform a first stirring and dispersion. The rotation speed of the first stirring and dispersion is 8000r / min, and the time of the first stirring and dispersion is 10min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system is 10%.

[0054] ② Add 4 parts of aluminum oxide nanosheets and 1 part of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 8000r / min, and the time of the second stirring dispersion is 10min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0055] ③ The papermaking material obtained in step ② is placed in a shaping mold (thickness 5 mm) and shaped and dried at 150°C for 12 hours, and then placed in an inert atmosphere furnace and carbonized at 900°C for 10 hours under an inert atmosphere (argon) to obtain a high-strength flexible thermal insulation material.

[0056] Example 4

[0057] ① Weigh 3 parts of phenolic fiber (diameter 300-800nm) and 17 parts of zirconia fiber (3-8μm), then add water and perform a first stirring and dispersion. The rotation speed of the first stirring and dispersion is 4000r / min, and the time of the first stirring and dispersion is 30min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system is 10%.

[0058] ② Add 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0059] ③ The papermaking material obtained in step ② is placed in a shaping mold (thickness 1 mm) and shaped and dried at 160°C for 12 hours, and then placed in an inert atmosphere furnace and carbonized at 700°C for 15 hours under an inert atmosphere (argon) to obtain a high-strength flexible thermal insulation material.

[0060] Example 5

[0061] Embodiment 5 is substantially the same as Embodiment 4, except that:

[0062] ② Add 1.5 parts of potassium hexatitanate K2Ti6O to the first dispersed system obtained in step ① 13 Nanowires, 2 parts of alumina nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are subjected to a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, the time of the second stirring dispersion is 6min, and a second dispersion system is obtained; then the second dispersion system is paper-made to obtain a paper-made material.

[0063] Example 6

[0064] Embodiment 6 is substantially the same as Embodiment 4, except that:

[0065] ② Add 3 parts of potassium hexatitanate K2Ti6O to the first dispersed system obtained in step ① 13 Nanowires, 2 parts of alumina nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are subjected to a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, the time of the second stirring dispersion is 6min, and a second dispersion system is obtained; then the second dispersion system is paper-made to obtain a paper-made material.

[0066] Example 7

[0067] Example 7 is substantially the same as Example 4, except that:

[0068] ② Add 0.5 parts of potassium hexatitanate K2Ti6O to the first dispersed system obtained in step ① 13 Nanowires, 2 parts of alumina nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are subjected to a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, the time of the second stirring dispersion is 6min, and a second dispersion system is obtained; then the second dispersion system is paper-made to obtain a paper-made material.

[0069] Example 8

[0070] Embodiment 8 is substantially the same as Embodiment 4, except that:

[0071] ② Add 1.5 parts of titanium dioxide TiO2 nanowires, 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion. The rotation speed of the second stirring dispersion is 4000 r / min, and the time of the second stirring dispersion is 6 min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0072] Comparative Example 1

[0073] ① Weigh 3 parts of phenolic fiber (diameter 300-800nm) and 17 parts of zirconia fiber (3-8μm), then add water and perform a first stirring and dispersion. The rotation speed of the first stirring and dispersion is 4000r / min, and the time of the first stirring and dispersion is 30min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system is 10%.

[0074] ② Add 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0075] ③ The papermaking material obtained in step ② is placed in a shaping mold (thickness 1 mm) and shaped and dried at 160°C for 12 hours, and then placed in an inert atmosphere furnace and carbonized at 700°C for 15 hours under an inert atmosphere (argon) to obtain a thermal insulation material.

[0076] Comparative Example 2

[0077] ① Weigh 20 parts of zirconium oxide fibers (3-8 μm), add water and perform a first stirring dispersion. The speed of the first stirring dispersion is 4000 r / min and the time of the first stirring dispersion is 30 min to obtain a first dispersion system. The total mass percentage of zirconium oxide fibers contained in the first dispersion system is 10%.

[0078] ② Add 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0079] ③ The papermaking material obtained in step ② was placed in a shaping mold (thickness 1 mm) and shaped and dried at 160° C. for 12 hours to obtain a thermal insulation material.

[0080] Comparative Example 3

[0081] ① Weigh 3 parts of phenolic fiber (diameter 300-800nm) and 17 parts of zirconia fiber (3-8μm), then add water and perform a first stirring and dispersion. The rotation speed of the first stirring and dispersion is 4000r / min, and the time of the first stirring and dispersion is 30min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconia fiber in the first dispersion system is 10%.

[0082] ② Add 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0083] ③ The papermaking material obtained in step ② was placed in a shaping mold (thickness 1 mm) and shaped and dried at 160° C. for 12 hours to obtain a thermal insulation material.

[0084] Comparative Example 4

[0085] ① Weigh 3 parts of carbon fiber (diameter 300-800nm) and 17 parts of zirconium oxide fiber (3-8μm), then add water and perform the first stirring and dispersion. The rotation speed of the first stirring and dispersion is 4000r / min, and the time of the first stirring and dispersion is 30min to obtain a first dispersion system; the sum of the mass percentages of phenolic fiber and zirconium oxide fiber in the first dispersion system is 10%.

[0086] ② Add 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0087] ③ The papermaking material obtained in step ② was placed in a shaping mold (thickness 1 mm) and shaped and dried at 160° C. for 12 hours to obtain a thermal insulation material.

[0088] Comparative Example 5

[0089] ① Weigh 17 parts of zirconium oxide fibers (3-8 μm), add water and perform a first stirring dispersion. The speed of the first stirring dispersion is 4000 r / min and the time of the first stirring dispersion is 30 min to obtain a first dispersion system. The total mass percentage of zirconium oxide fibers contained in the first dispersion system is 10%.

[0090] ② Add 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) to the first dispersed system obtained in step ① and perform a second stirring dispersion, the rotation speed of the second stirring dispersion is 4000r / min, and the time of the second stirring dispersion is 6min to obtain a second dispersed system; then the second dispersed system is paper-made to obtain a paper-made material.

[0091] ③ The papermaking material obtained in step ② was placed in a shaping mold (thickness 1 mm) and shaped and dried at 160° C. for 12 hours to obtain a thermal insulation material.

[0092] The present invention conducts tensile strength, bending radius and 400°C thermal conductivity tests on the high-strength flexible thermal insulation materials prepared in each embodiment and the thermal insulation materials prepared in each comparative example, and the results are shown in Table 1; It can be seen from Table 1 that the high-strength flexible thermal insulation materials prepared in each embodiment of the present invention have high strength and good flexibility, and excellent thermal insulation performance.

[0093] Table 1: Mechanical and thermal performance results of the high-strength flexible thermal insulation materials prepared in each embodiment and the thermal insulation materials prepared in each comparative example.

[0094]

[0095] In Table 1, the symbol “-” indicates that the performance index has not been tested; the “parts” involved in the embodiments of the present invention and the comparative examples all refer to “parts by weight”, and the unit, for example, can be uniformly taken as weight units such as “g” or “kg”.

[0096] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-strength flexible thermal insulation material, characterized in that: The method comprises the following steps: (1) subjecting a system comprising phenolic fiber, zirconium oxide fiber and water to a first stirring dispersion to obtain a first dispersed system; (2) adding alumina nanosheets and phosphate solution to the first dispersed system and performing a second stirring dispersion to obtain a second dispersed system, and then papermaking the second dispersed system to obtain a papermaking material; (3) The papermaking material is placed in a shaping mold for shaping and drying, and then carbonized under an inert atmosphere to obtain a high-strength flexible thermal insulation material.

2. The preparation method according to claim 1, characterized in that: In step (1): The mass ratio of the zirconium oxide fiber to the phenolic fiber is (4-19):

1.

3. The preparation method according to claim 1, characterized in that: In step (1): The diameter of the zirconia fiber is 1 to 10 μm; and / or The diameter of the phenolic fiber is 200-1000nm.

4. The preparation method according to claim 1, characterized in that: In step (1): The rotation speed of the first stirring and dispersing is 4000-10000 r / min, and the time of the first stirring and dispersing is 2-30 min.

5. The preparation method according to claim 1, characterized in that: In step (2): The mass ratio of the aluminum oxide nanosheets to the phosphate solution is (1-4):(1-9); and / or The phosphate solution is an aluminum dihydrogen phosphate solution, and the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 20-50%.

6. The preparation method according to claim 1, characterized in that: In step (2): The rotation speed of the second stirring and dispersing is 4000-10000 r / min, and the time of the second stirring and dispersing is 1-10 min.

7. The preparation method according to claim 1, characterized in that: In step (3): The temperature of the shaping and drying is 120-200° C.; and / or The thickness of the shaping die is 0.5-5 mm.

8. The preparation method according to claim 1, characterized in that: In step (3): The carbonization temperature is 500-900° C., and the carbonization time is 10-20 hours.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (2): Potassium hexatitanate K2Ti6O is also added to the first dispersed system. 13 Nanowires; Preferably, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowires to the aluminum oxide nanosheets is 1:(1-2).

10. A high-strength flexible thermal insulation material produced by the production method according to any one of claims 1 to 9.